Histories of water and fisheries management in Northern Ghana - Jennifer Hauck; Eva Youkhana (University of Bonn, Center for Development Research (ZEF), 2008)
To counteract low water productivity in many developing countries, international donors promote community-based management. This practice was meant to replace top-down governmental approaches. In Ghana, the water sector has come under review in the 1990s. Institutions have been decentralized, and management tasks transferred to communities, associations, and private-sector entities. While assigning ownership and responsibilities to communities is feasible for rural water management, the paper shows, that policy makers and practitioners tend to ignore the historical background of existing structures and antagonisms of traditional and present management systems. Implementation strategies are thus prone to failure. The paper analyses the administrative history of water governance in Ghana, and related problems to date. The case study on fisheries management has its setting in the Upper East Region of Ghana, where people use reservoirs to improve their livelihoods through irrigation, cattle watering, and fisheries. In the course of rehabilitation projects, rights and responsibilities of management have been handed over to user groups or associations and village committees. Clashing traditional, governmental, and participatory management strategies overtax communities to cope with responsibilities. Conflicts, mistrust and overexploitation are some of the consequences.
urn:nbn:de:101:1-2009030243
Keywords: 630; Historic coherences; water conflicts; Ghana; community based management